Integrated environmental research and networking of economy and information in rural areas of Finland - Matti Luostarinen (Scientific Agricultural Society of Finland, 1998)
This article uses material from many extensive research projects starting from the construction of the electric power supply network and its water supply systems in northern Finland in 1973-1986, to the Agropolis agricultural strategy and networking for the Loimijoki project. A list of the material and references of the publications is available in Agronet on the Internet. All these projects applied integrated environmental research covering biology, the natural sciences, social sciences, and planning methodology. To be able to promote sustainable agriculture and rural development there is a pressing need to improve research methodology and applications for integrated environmental research. This article reviews the philosophy and development of the theory behind integrated environmental research and the theory of network economy.